Papuloerythroderma of Ofuji: A first case report from Indonesia - Regina, Graciella; Paramita, Listya; Radiono, Sunard; Wirohadidjojo, Yohanes Widodo; Faber, William R (Journal of General - Procedural Dermatology and Venereology Indonesia, 2016)
Papuloerythroderma (PE) is a rare skin disease which was first described by Ofuji et al. in 1984, with a typical sign that the lesions spare the large cutaneous folds, known as the deck chair sign. Due to its recent identification, this disease is still underrecognized and may lead to misdiagnosis. We reported the first case report of PE of Ofuji from Indonesia in which the diagnosis was delayed for two years. Besides the deck chair sign in the large cutaneous fold, we also found that the area between and above his eyebrows that was relatively spared in contrast to the sparing of the cutaneous folds, and it may be considered as pseudo-deck chair sign. The patient showed good response with combination therapy of phototherapy with Narrow-Band Ultraviolet B (NBUVB), oral methotrexate, and corticosteroids. The deck chair sign disappeared after six months therapy, but the patient’s skin was still xerotic.